STUDI NUMERIK SIMULASI ROBOT PEMBERSIH KACA PADA GEDUNG BERTINGKAT - Balisranislam, Balisranislam; Sutantra, I Nyoman; Sampurno, Bambang; Sufyan Hadi, Herry (J-Eltrik, 2019)
Buildings have priority to support the comfort and public relations of air circulation system and natural lighting, where the most widely used system is glass. In general, the process of cleaning glass in multi-storey building using conventional labor is by human labor. This process is relatively simple but has a loss in work accidents. Therefore, this study discusses glass cleaning robots. the working system of moving the wheel of the robot directly, and the control system using PID control. Tuning PID using Zigler-Nichols and Find Tuning methods with Simulink. Based on the results of PID Controller Calculation using Zigler Nichols method, the value obtained Kp = 0,01446, Ki = 0,0000026, and Kd = 9524,35. While calculation of PID controller using PID tuning with simulink, obtained value Kp = 19,365, Ki = 13,115, and Kd = 5,699. The speed control system using the Zigler-Nichols method does not produce a good response, because the resulting response is still unstable. While PID control using Tuning can produce a good response with up time can be achieved within 1.39 seconds, over shoot by 8% and the exact completion time is 5 secondsÂ